Status Hukum dan Hak Anak Dari Perkawinan Wanita Hamil Dalam Perspektif Mazhab Syafi'i dan Hukum Positif - Mara Sutan Rambe (SALAM: Jurnal Sosial dan Budaya Syar-i, 2017)
Abstract.The legal status and rights of the child of the marriage of a pregnant woman according to the Shafi'i School are if the child is born less than six months from a legitimate marriage or the possibility of prior bodily relationships, then the child is an illegitimate child and only has a relationship to his mother and family her mother. However, if the child is born more than six months of pregnancy from a legal marriage or if there is a possible relationship, then the child is a legitimate child, so he has rights to his parents. UUP and KHI regulate that children born from the marriage of pregnant women due to zina are legitimate children, as long as the child is born from a legitimate marriage (article 42 UUP and article 99 points a KHI), so that he has rights that must be fulfilled by both her parents. However, if a child born due to adultery is not in a legal marriage, then the child only has a civil relationship to his mother as stated in article 43 (1) of the LoGA. However Article 43 (1) has a Judicial Review, so that a child born outside of marriage does not only have a civil relationship with his mother but also has a civil relationship with his biological father.Keywords: Legal Status, Children's Rights, Marriage of Pregnant Women Abstrak.Status hukum dan hak anak dari perkawinan wanita hamil menurut Mazhab Syafi’i adalah jika anak tersebut lahir kurang dari enam bulan dari perkawinan yang sah atau dimungkinkan adanya hubungan badan sebelumnya, maka anak tersebut adalah anak tidak sah dan hanya mempunyai hubungan nasab kepada ibunya dan keluarga ibunya. Namun, jika anak tersebut lahir lebih dari enam bulan masa kehamilan dari perkawinan sah atau dimungkinkan adanya hubungan badan, maka anak tersebut adalah anak sah, sehingga memiliki hak terhadap kedua orang tuanya. UUP dan KHI bahwa anak yang lahir dari perkawinan wanita hamil akibat zina adalah anak yang sah, sepanjang anak tersebut lahir dari perkawinan yang sah (pasal 42 UUP dan pasal 99 poin a KHI), sehingga ia memiliki hak-hak yang wajib dipenuhi oleh kedua orang tuanya. Namun jika anak yang lahir akibat zina tidak dalam ikatan perkawinan yang sah, maka anak tersebut hanya mempunyai hubungan perdata kepada ibunya saja sebagaimana yang tercantum dalam pasal 43 (1) UUPA. Namun Pasal 43 (1) ini telah Judicial riview, sehingga anak yang dilahirkan di luar perkawinan tidak hanya mempunyai hubungan perdata dengan ibunya tetapi juga mempunyai hubungan perdata kepada ayah biologisnya.Kata Kunci: Status Hukum, Hak Anak, Perkawinan Wanita Hamil